Effect of T6 Heat Treatment on Tensile Strength and Hardness of A356 Aluminum Alloy at 720°C Optimization: Pengaruh Perlakuan Panas T6 terhadap Kekuatan Tarik dan Kekerasan Paduan Aluminium A356 pada Optimasi Suhu 720°C - Wawan Budi; Johan Alfian Pradana; Bamban Handriyanto; Nazri Syah Rizan; Saiful Rowi; Ahmad Bazi Syarif (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2026)
This study aims to analyze the effect of T6 heat treatment on the mechanical properties of A356 aluminum alloy to determine the optimal processing condition. A356 aluminum is widely used in the automotive industry; however, its as-cast condition exhibits limited strength, requiring improvement through heat treatment processes. The research method involves varying T6 treatment temperatures at 690°C, 720°C, and 750°C, followed by tensile testing, hardness testing, and ANOVA statistical analysis. The results show that T6 treatment significantly improves mechanical properties compared to the as-cast condition, with the highest ultimate tensile strength of 28.3 kg/mm² achieved at 720°C. Hardness also reaches its maximum value at this temperature. However, increasing the temperature to 750°C leads to a decline in mechanical properties due to gas porosity formation that degrades microstructural integrity. ANOVA analysis confirms a significant effect of temperature on hardness (F = 287.300; p < 0.001). Therefore, 720°C is identified as the optimum condition for enhancing the mechanical performance of A356 alloy through T6 heat treatment.